2018
DOI: 10.1021/acs.jpcc.8b08089
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Spectra of Graphene in Far- and Deep-Ultraviolet Region: Attenuated Total Reflection Spectroscopy and Quantum Chemical Calculation Study

Abstract: We measured the electronic spectra of graphene nanostructures (flakes and platelets) extending into the far-ultraviolet (FUV) region by attenuated total reflection far- and deep-ultraviolet (ATR–FUV–DUV) spectroscopy in the region of 2.76–8.55 eV (450–145 nm). The major absorption of graphene appears in the DUV region (4.7 eV), as already reported; however, we observed a new peak in the FUV region, visible clearly in the case of flakes at 7.5–7.7 eV (165–161 nm) and less pronounced in the spectrum of the plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…In the reviewed study, the ZINDO/s method was used to obtain relative excitation energies, which were in good agreement with the observed peaks in the experimental spectra, with additional linear scaling of the calculated vertical excitation energies 54,107 In the case of ATR-FUV-DUV study of graphene nanostructures, wavelength scaling yielded a remarkably good agreement with experimental data, as demonstrated in Fig. 21.…”
Section: Exploration Of the Electronic Structure Of Ultrathin Materia...supporting
confidence: 62%
See 4 more Smart Citations
“…In the reviewed study, the ZINDO/s method was used to obtain relative excitation energies, which were in good agreement with the observed peaks in the experimental spectra, with additional linear scaling of the calculated vertical excitation energies 54,107 In the case of ATR-FUV-DUV study of graphene nanostructures, wavelength scaling yielded a remarkably good agreement with experimental data, as demonstrated in Fig. 21.…”
Section: Exploration Of the Electronic Structure Of Ultrathin Materia...supporting
confidence: 62%
“…108,110,111 The examination of these experimental spectra with aid from quantum chemical calculations study also revealed a dependence of the 165 nm peak on the graphene morphology. 107 The presence of the DUV peak in the spectra of graphene and other nanocarbon structures has been previously documented, but its reported position has varied widely, ranging from 227-260 nm (4.65-5.46 eV). 112,113 The debate surrounding the case of graphite highlights the need for continued experimental and computational investigations into the specifics of FUV-DUV absorption characteristics in carbon nanostructures.…”
Section: Electronic Properties Of Graphene Particles and Polymergraph...mentioning
confidence: 96%
See 3 more Smart Citations